EDE TERÉNYI IS 80 YEARS OLD. A LIFE SERVING ART, TEACHING AND THE MUSICAL SCIENCES - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica, 2015)
Author of several hundred musical works, Ede Terényi (b. 1935) is a weighty and original personality within the cultural life of Transylvania. Composing did not mean to him merely a process of artistic creation based on incidental mathematical formulas. His entire being is continuously living within and through music. Music is the meaning of his life, his motivation for existence. He is a man with great sensitivity who lets himself be inspired by a word, an image, a gesture, a verse or a wonderful piece of music he has just heard. His works have been created by spontaneous inspiration, on the one hand and by a steady, conscious work on fine tuning his music, everything that belongs to the so called craftsmanship in composing, on the other.